Identifying disease risk hotspots in buffalo meat (Carabeef) value chain - BARDHAN, D; KUMAR, S; KUMAR, S; KUMAR, N; KHAN, R; TALUKDER, S; MENDIRATTA, S K (The Indian Journal of Animal Sciences, 2022)
The study was carried out to quantitatively map and analyse buffalo meat value chains in Uttar Pradesh state ofIndia. The chain actors identified were farmers, peri-urban and urban dairies, aggregators, traders/sub-traders,retailers, restaurants/ roadside stalls and export-oriented abattoirs. Mapping exercise shows that aggregators constitutethe main link between farmers and live animal markets and account for 72% of the total flow of buffaloes tolivestock markets. Sub-traders/traders ship the bulk of the flow from markets to abattoirs. Of the total meat produced,87% is shipped directly to importing countries and the rest (12%) to retailers (local and from other districts). Theresults of quantitative value chain mapping along with the risk pathways in the value chain (as identified by theresearch team) were presented to a panel of experts for rating of each risk factor on two dimensions, viz. ‘likelihoodof risk factor causing unwanted outcome’(introduction of pathogenic organism) and ‘impact of unwanted outcome’(quality deterioration and adverse health implications for consumers of final meat products), each on a three-pointcontinuum (low, medium and high). The ratings were then used to prepare a two-dimensional risk matrix havingtotal of nine cells. The above exercise identified total of seven major disease risk hotspots in buffalo meat valuechain. Overall, this study provided qualitative evidence of importance of adopting value chain approach in diseaserisk mitigation, by identifying structural deficiencies and vulnerabilities.